1999
DOI: 10.1017/s096719949900057x
|View full text |Cite
|
Sign up to set email alerts
|

Influences of zinc on fertilisation and development of bovine oocytes in vitro

Abstract: The effects of zinc (as ZnCl2) on in vitro production of bovine embryos (IVMFC) and components of the procedure, that is in vitro oocyte maturation (IVM), fertilisation (IVF) and embryo development in culture (IVC), and the effect of added zinc on sperm motility were studied. Immature cumulus oocyte complexes (COCs) were aspirated from ovarian follicles (2-5 mm diameter) at slaughter, and matured, fertilised and cultured in chemically defined conditions. The presence of zinc (10, 100 or 1000 μg added per milli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 51 publications
0
15
0
1
Order By: Relevance
“…The remaining concentrations of zinc we found in the media after swim‐up preparation could be a significant negative factor for oocyte maturation (bovine: Stephenson and Brackett, 1999), fertilization (mouse: Aonuma et al, 1981), and early embryonic development (mouse: Vidal and Hidalgo, 1993; bovine: Stephenson and Brackett, 1999; Table 4). Results also indicate that, among noncapacitated mammalian sperm, presence of zinc can inhibit the acrosome reaction (mouse: Aonuma et al, 1978, 1982; hamster: Andrews and Bavister, 1989; Andrews at al, 1994; human: Riffo et al, 1992) and that presence of seminal plasma constituents in the “insemination” medium can decrease fertilization during in vitro fertilization in mammals (hamster: Tsunoda and Chang, 1977; mouse: Quinn et al, 1982; Quinn and Begley, 1984; human spermatozoa and hamster oocytes: Van der Ven et al, 1983; boar: Suzuki et al, 2002) and fowls (Blesbois and de Reviers, 1992).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The remaining concentrations of zinc we found in the media after swim‐up preparation could be a significant negative factor for oocyte maturation (bovine: Stephenson and Brackett, 1999), fertilization (mouse: Aonuma et al, 1981), and early embryonic development (mouse: Vidal and Hidalgo, 1993; bovine: Stephenson and Brackett, 1999; Table 4). Results also indicate that, among noncapacitated mammalian sperm, presence of zinc can inhibit the acrosome reaction (mouse: Aonuma et al, 1978, 1982; hamster: Andrews and Bavister, 1989; Andrews at al, 1994; human: Riffo et al, 1992) and that presence of seminal plasma constituents in the “insemination” medium can decrease fertilization during in vitro fertilization in mammals (hamster: Tsunoda and Chang, 1977; mouse: Quinn et al, 1982; Quinn and Begley, 1984; human spermatozoa and hamster oocytes: Van der Ven et al, 1983; boar: Suzuki et al, 2002) and fowls (Blesbois and de Reviers, 1992).…”
Section: Discussionmentioning
confidence: 95%
“…Contamination by semen constituents can hinder or decrease sperm hyperactivation and acrosome reaction (Andrews and Bavister, 1989; Han et al, 1990; Cross, 1993; Andrews et al, 1994; Cross, 1996; Cross and Mahasreshti, 1997; Mortimer et al, 1998), and zinc in particular hampers fertilization and early embryonic development (Tsunoda and Chang, 1977; Quinn et al, 1982; Van der Ven et al, 1983; Quinn and Begley, 1984; Blesbois and de Reviers, 1992; Vidal and Hidalgo, 1993; Stephenson and Brackett, 1999; Suzuki et al, 2002). In clinical practice, there are 2 main techniques to separate spermatozoa from seminal plasma: those based on sperm mobility (“swim‐up”) and gradient centrifugation.…”
mentioning
confidence: 99%
“…More importantly, microtubules, a component of the cytoskeleton, are the major constituents of spindles that are used to pull apart eukaryotic chromosomes during mitosis and meiosis. Moreover, Stephenson et al [44] reported that the zinc level would affect bovine oocyte maturation and fertilization in vitro. Furthermore, Kong et al demonstrated that rapid cellular zinc influx regulates early mammalian development during the oocyte-to-egg transition through modulation of the meiotic cell cycle [45].…”
Section: Discussionmentioning
confidence: 99%
“…Sperm can induce Zn 2+ release from the oocyte cortex [ 111 , 112 ], leading to proteinase inhibition; as a result, sperm that are still bound to the ZP became decapacitated, and polyspermy was prevented. It was also suggested that Zn 2+ inhibits sperm chemoattraction to the egg induced by oocyte-secreted progesterone in human, mouse and rabbit sperm [ 113 ], and the addition of Zn 2+ (~0.1 mM) to bovine in vitro fertilization (IVF) medium reduces the fertilization rate [ 114 ]. Additionally, blockers of Zn 2+ -dependent metalloproteases inhibit sperm passage via the cumulus oophorus in porcine IVF [ 115 ].…”
Section: Zinc and Fertilitymentioning
confidence: 99%